2022
DOI: 10.1292/jvms.22-0013
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the neurological effects of clothianidin exposure at the no-observed-adverse-effect level (NOAEL) using two-photon microscopy <i>in vivo</i> imaging

Abstract: Neonicotinoid pesticides (NNs) cause behavioral abnormalities in mammals, raising concerns about their effects on neural circuit activity. We herein examined the neurological effects of the NN clothianidin (CLO) by in vivo Ca 2+ imaging using two-photon microscopy. Mice were fed the no-observed-adverse-effect-level (NOAEL) dose of CLO for 2 weeks and their neuronal activity in the primary somatosensory cortex (S1) was observed weekly for 2 weeks. CLO exposure caused a sustained influx of Ca 2+ in neurons in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…However, imidacloprid and acetamiprid, which are NNs, were found to have excitatory effects on mammalian cerebellar neurons via nAChRs [ 24 ]. Subsequently, questions arose about the reproductive toxicity of NNs [ 17 , 21 , 25 , 47 , 53 ], their neurotoxicity and involvement in cognitive‒emotional alterations [ 14 , 16 , 17 , 18 , 20 , 26 , 27 , 33 , 44 , 45 , 55 ], and their safety, even at the no-observed-adverse-effect level (NOAEL). Recently, subchronic exposure to clothianidin (CLO), a type of NN, has been reported to disrupt the intestinal microbiota of rats [ 35 ] and mice [ 30 , 56 ].…”
mentioning
confidence: 99%
“…However, imidacloprid and acetamiprid, which are NNs, were found to have excitatory effects on mammalian cerebellar neurons via nAChRs [ 24 ]. Subsequently, questions arose about the reproductive toxicity of NNs [ 17 , 21 , 25 , 47 , 53 ], their neurotoxicity and involvement in cognitive‒emotional alterations [ 14 , 16 , 17 , 18 , 20 , 26 , 27 , 33 , 44 , 45 , 55 ], and their safety, even at the no-observed-adverse-effect level (NOAEL). Recently, subchronic exposure to clothianidin (CLO), a type of NN, has been reported to disrupt the intestinal microbiota of rats [ 35 ] and mice [ 30 , 56 ].…”
mentioning
confidence: 99%
“…Although NNs have been considered safe for mammals because their affinity for nAChRs is tens to hundreds of times higher in insects than in mammals, recent studies in mammals, primarily rodents, have indicated that nAChRs induce cognitive‒emotional changes, such as anxiety-like behavior and decreased spontaneous locomotor activity [ 8 , 9 , 19 , 20 , 21 , 22 , 24 , 25 , 37 , 40 , 44 , 51 , 52 , 53 , 55 , 56 , 62 ]. However, only a limited number of investigations on memory and learning in mammals have been reported, and the severity of effects at trace concentrations, along with the underlying mechanisms, remain unclear.…”
mentioning
confidence: 99%
“…After the RR study, the cerebellum of some mice was excised and frozen in liquid nitrogen. RNA extraction, quality analysis, and microarray analysis were performed as previously reported [ 44 ], with n=2 in the R0 group and n=2 in the R50 group. The microarray data (.CEL files) were deposited in a public database (Gene Expression Omnibus, accession number: GSE251773).…”
mentioning
confidence: 99%
“…NNs were thought to be safe for mammals because their affinity for nAChRs is tens to hundreds of times higher than that of mammals [ 38 ]. Recently, however, studies exposing birds and mammals to no-observed-adverse-effect-levels (NOAELs) of NNs have revealed that NNs affect reproduction, the thymus, gut flora, and neurobehavior in higher vertebrates [ 4 , 14 , 21 , 23 , 26 ]. Moreover, it is clear that NNs are routinely transferred from mother to offspring, considering the rapid transfer of clothianidin (CLO), a type of NN, and its metabolites from mother to fetus via the placenta [ 27 ]; the metabolism and concentration of CLO in mothers and its rapid transfer into breast milk [ 34 ]; and the detection of NNs in the urine of Japanese adults, children, and newborns [ 17 , 18 , 28 , 39 ].…”
mentioning
confidence: 99%